The Significance of Decarbonization in Anesthesia - Lertkovit, Saranya; Aekta, Amornrat; Apiwatchatchawan, Chotima; Vichitvejpaisal, Phongthara (Siriraj Medical Bulletin, 2021)
Naturally, greenhouse gas has crucial effect on the world climate towards extending the creature lifespan. However, the man-made wastes from deforestation, inefficient use of limiting resources as well as overwhelming industrial products and agricultural produces yield critically toxic environment and global warming for decades. Eventually, human beings should be aware of the application to a sophisticated knowledge of technology in minimizing carbon emission to the earth’s atmosphere under the principle standard of Life Cycle Assessment known as Decarbonization. In daily practice, anesthesia personnel have substantial role not only to take care their patients with close monitoring but also to reduce carbon production. In addition, they ought to choose regional anesthesia and low flow technique as first priority, avoidance of medical equipment, drugs and gases that produce high carbon footprint, global warming potential, carbon lifetime and persists bioaccumulation toxicity to the benefits of global environment.